1998
DOI: 10.1007/s004420050519
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in plant size and relative growth rate in Arabidopsis thaliana

Abstract: Latitude is an important determinant of local environmental conditions that affect plant growth. Forty ecotypes of Arabidopsis thaliana were selected from a wide range of latitudes (from 16°N to 63°N) to investigate genetic variation in plant size and relative growth rate (RGR) along a latitudinal gradient. Plants were grown in a greenhouse for 31 days, during which period three consecutive harvests were performed. Plants from high latitudes tended to have smaller plant size in terms of seed size, cotyledon wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
164
2
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 33 publications
31
164
2
2
Order By: Relevance
“…Arabidopsis is widely distributed in northern temperate regions and RGRs and NARs of ecotype accessions both correlate negatively with latitude of origin (Li et al, 1998). Our conclusion that NAR determined the RGR differential between Col-0 and NahG accords with the correlation between these two growth parameters in the ecotypes studied by Li et al (1998).…”
Section: Discussionsupporting
confidence: 68%
“…Arabidopsis is widely distributed in northern temperate regions and RGRs and NARs of ecotype accessions both correlate negatively with latitude of origin (Li et al, 1998). Our conclusion that NAR determined the RGR differential between Col-0 and NahG accords with the correlation between these two growth parameters in the ecotypes studied by Li et al (1998).…”
Section: Discussionsupporting
confidence: 68%
“…Similarly, leaf production and plant size decreased along latitude that is correlated with a decrease in temperature at a larger scale (Li et al, 1998). Note that in these studies and in our study, rosette leaf number and rosette diameter after a defined period of time are used as measures of growth; in our study, rosette leaf number and rosette diameter after 3 weeks were not correlated with flowering time (Supplementary Table S5).…”
Section: Discussionsupporting
confidence: 50%
“…In A. thaliana, specific leaf area decreases with latitude of origin (Li et al, 1998). In other species, specific leaf area was shown to decrease with either altitude or drought or with both factors (e.g., Hovenden and Vander Schoor, 2004;Gonzalo-Turpin and Hazard, 2009;Ramirez-Valiente et al, 2010;Scheepens et al, 2010) and this is also the pattern observed between species (Körner, 1999(Körner, , 2003Niinemets, 2001;Poorter et al, 2009).…”
Section: Discussionmentioning
confidence: 76%
“…The variation in mean RGR over a period of 4 weeks was significant in C. virosa populations (Table 2) and similar to the intraspecific variation in A. thaliana and other herbaceous plants (Meerts and Garnier, 1996;Li et al, 1998;Van Rijn et al, 2000). The instantaneous root: shoot ratio in any individual plant is subjected to genetic, ontogenetic, and environmental control (Gedroc et al, 1996).…”
Section: Variation In Seed Size and Growth Processsupporting
confidence: 52%
“…plant size and relative growth rate of Arabidopsis thaliana (Li et al, 1998), germination and seedling desiccation tolerance of Hordeum spontaneum local ecotypes in Israel (Gutterman and Gozlan, 1998), flowering time in some A. thaliana ecotypes (Nordborg and Bergelson, 1999), dormancy and freezing tolerance in Betula pendula Roth (Li et al, 2003), and physiological and growth responses in Populus davidiana ecotypes (Zhang et al, 2005)). Those studies established the patterns of responses to the environment and adaptation traits to a given environment.…”
Section: Introductionmentioning
confidence: 99%